Dielectric pads and low‐ B1+ adiabatic pulses: Complementary techniques to optimize structural T1w whole‐brain MP2RAGE scans at 7 tesla. Issue 4 (5th November 2013) - O'Brien, Kieran R.; Magill, Arthur W.; Delacoste, Jean; Marques, Jose P.; Kober, Tobias; Fautz, Hans‐Peter; Lazeyras, Francois; Krueger, Gunnar
<x xml:space="preserve">Abstract</x> Purpose To evaluate the combination of low‐B1+ adiabatic pulses and high permittivity (εr ≈ 165) dielectric pads effectiveness to reproducibly improve the inversion efficiency for whole‐brain MP2RAGE scans, at ultra‐high field. Materials and Methods Two low‐B1+ adiabatic pulses, HS8 and TR‐FOCI, were compared with the conventional HS1 adiabatic pulse in MP2RAGE acquisitions of four subjects at 7 Tesla. The uniform MP2RAGE images were qualitatively assessed for poor inversion artifacts by trained observers. Each subject was rescanned using dielectric pads. Eight further subjects underwent two MP2RAGE scan sessions using dielectric pads and the TR‐FOCI adiabatic pulse. Results The HS8 and TR‐FOCI pulses improved inversion coverage in all subjects compared with the HS1 pulse. However, in subjects whose head lengths are large (≥136 mm) relative to the coil's z‐coverage, the B1+ field over the cerebellum was insufficient to cause inversion. Dielectric pads increase the B1+ field, by ∼50%, over the cerebellum, which in conjunction with the TR‐FOCI pulse, reproducibly improves the inversion efficiency over the whole brain for subjects with head lengths ≤155 mm. Minor residual inversion artifacts were present in three of eight subjects (head lengths ≥155 mm). Conclusion The complementary techniques of low‐B1+ adiabatic RF pulses and high permittivity dielectric pads allow whole‐brain structural T1w images to be reliably acquired at ultra‐high field. J. Magn. Reson. Imaging 2014;40:804–812. © 2013 Wiley Periodicals, Inc.